Varieties of capitalism, varieties of crisis response Bank bailouts in comparative perspective - Sebastian Schneider (Freie Universität Berlin, Center for International Political Economy, 2014)
Given recent history it may be necessary to recall that the so-called Great Recession we have been witnessing for more than five years now was, first and foremost, a crisis of financial markets. One reason for rising debt levels at the outset of the crisis have been massive government expenditures to bail out struggling and even failing banks. Yet, I argue that it falls short of a satisfactory explanation to simply view political action as a rational response to "objective" political and economic problems. Therefore, the fundamental question that underlays this study is: How did different institutional settings influence diverging policy reactions to the financial crisis? To answer this question, this study compares bank bailouts in France, Germany and the United Kingdom. Drawing upon the Varieties of Capitalism literature, I identify four central, national institutions that have influenced political decision-making during the financial crisis: the political system, traditions of market intervention, economic discourse and banking and financial systems. The French president, Nicolas Sarkozy, reverting to France's dirigiste tradition and resorting to a dense elitist network, used bank bailouts to support the French financial industry and to create "national champions". This sort of policy was accompanied by a non-liberal discourse criticising "excessive" financial markets. In Germany, on the other hand, the government deliberated with a broad coalition of political and market actors to create a bailout programme aiming at sustaining bank lending to the industry. However, market actors were criticised on a moral and ethical basis and the ordo-liberal state was considered as a necessary corrective safeguarding true economic freedom. Finally, the UK's "elected dictator", Prime Minister Gordon Brown, used his political power and involved his close political allies to carry out a bailout programme that was predominantly designed to defend the international competitiveness of the British financial industry. Albeit market intervention was inevitable it was announced as being temporarily and leaving as much problem solving as possible to the markets. – – Angesichts der jüngeren Geschichte scheint die Erinnerung notwendig, dass die derzeitige Wirtschaftskrise zunächst als Bankenkrise begann. Zur Beilegung dieser Krise und zur Rettung zahlreicher Kreditinstitute, setzten die Regierungen in Europa und Nordamerika Summen bisher ungeahnten Ausmaßes ein. Diese Bankenrettungsprogramme waren jedoch mehr als nur eine rationale Lösung für bestehende wirtschaftliche Probleme. Wie diese Arbeit zeigt, hatten nationale Institutionen großen Einfluss auf politische Entscheidungen im Rahmen der Bankenrettung. Ein Vergleich zwischen Deutschland, Frankreich und Großbritannien zeigt, welche historisch gewachsenen Institutionen dabei eine entscheidende Rolle spielten und wie sie das taten. Vier zentrale, nationale Institutionen lassen sich mithilfe der Varieties of Capitalism-Literatur identifizieren: Das politische System, des Verhältnis Staat-Markt, der ökonomische Diskurs sowie das Banken- und Finanzsystem. Die deutsche Regierung verhandelte die diversen Bankenrettungen mit einer breiten Koalition politischer und Marktakteure, mit dem Ziel, die Kreditvergabe an die heimische Industrie zu stabilisieren. Begleitet wurde dieses Vorgehen von einem ordo-liberalen Diskus. Die Bankenrettung in Frankreich hingegen wurde durch den Präsidenten dominiert, welcher dabei auf ein Netzwerk aus politischen und Wirtschaftseliten zurückgriff, um "nationale Champions" zu schaffen. Hinzu kam ein kapitalismuskritischer öffentlicher Diskurs. In Großbritannien spielte Premier-Minister Gordon Brown eine beinahe ebenso dominante Rolle. Mit dem vorrangigen Ziel, die Wettbewerbsfähigkeit des Finanzstandortes London zu erhalten, griffen in Groß-Britannien vor allem Marktmechanismen und ein neoliberaler Diskurs.
urn:nbn:de:101:1-2014121123512
Keywords: 330